2010
DOI: 10.5174/tutfd.2010.04370.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Effecting Job Satisfaction Among Academic Staff

Abstract: Original Article ÖZET Amaç: Akademisyenlik özveri ve dolayısıyla mesleki tatmin gerektiren alanlardan biridir. Bu çalışmada Trakya Üniversitesinde çalışan tüm akademik personelin sosyodemografik özellikleri ile iş doyumu düzeylerinin araştırılması amaçlanmıştır.Gereç ve Yöntemler: Araştırmada Minnesota Tatmin Ölçeği kısa formunu içeren bir anket kullanıldı. Verilerin değerlendirilmesinde frekans tabloları, çapraz tablolar, Pearson Ki-kare, Exact Ki-kare, Kruskal Wallis ve Dunn çoklu karşılaştırma testleri ve "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…It can be said that high income and high education level increases the job satisfaction of the coaches and this leads to high performance. Similarly, Dagdeviren et al (2011) found that job satisfaction increased as the income and education level of Yildiz, S.M., Gunel, I., & Duyan, M. (2019). Investigation of the effect of job stress on sport coaches' job performance.…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…It can be said that high income and high education level increases the job satisfaction of the coaches and this leads to high performance. Similarly, Dagdeviren et al (2011) found that job satisfaction increased as the income and education level of Yildiz, S.M., Gunel, I., & Duyan, M. (2019). Investigation of the effect of job stress on sport coaches' job performance.…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…Bununla birlikte, kayak eğitmenlerinin iş doyumlarının "hizmet süresi" değişkenine göre anlamlı farklılık göstermediği sonucuna ulaşılmıştır. İş doyumu araştırmalarında hizmet süresinin farklılık göstermediği bulgulara rastlamak mümkündür (Avşaroğlu, Engin Deniz & Kahraman, 2005;Dağdeviren, Musaoğlu, Ömürlü & Öztora, 2011). Örneklem grubunun çalışma ortamları ve koşulları dikkate alındığında, yaşadıkları ve yaşanması gereken hayatları arasındaki farklılıkları kompanse edebilme becerilerinin arttığı söylenebilmektedir.…”
Section: Tartişma Ve Sonuçunclassified
“…While the literature contains studies that examine the business satisfaction of academic staff and the life satisfaction separately (Akman, Kelecioglu and Bilge, 2006;Dagdeviren, Musaoglu and Omurlu, 2011;Cavus and Abdildaev, 2014;Ulker Tumlu and Recepoglu, 2013;Demir and Akbaba, 2018) business satisfaction and life satisfaction is limited and no work has been found in academics in the health sciences.…”
Section: Introductionmentioning
confidence: 99%